Digital Atlas of Anatomical Subdivisions and Boundaries of the Rat Hippocampal Region - Kjonigsen, Lisa J.; Leergaard, Trygve B.; Witter, Menno P.; Bjaalie, Jan G. (Frontiers in Neuroinformatics, 2011)
The rat hippocampal region is frequently studied in relation to learning and memory processes and brain diseases. The region is complex, consisting of multiple subdivisions that are challenging to delineate anatomically. Published atlases of the rat brain typically lack the underlying histological criteria necessary to identify boundaries, and textbooks descriptions of the region are often inadequately illustrated and thus difficult to relate to experimental data. An overview of both anatomical features and criteria used to delineate boundaries is required to assign location to experimental material from the hippocampal region. To address this issue, we have developed a web-based atlas application in which images of histological sections are integrated with new and up-to-date criteria for subdividing the rat hippocampus formation, fasciola and associated parahippocampal regions. The atlas application consists of an interactive image viewer with high-resolution images of an extensive series of sections stained for NeuN, calbindin, and parvalbumin, and an index of structures with detailed descriptions of the criteria used to define the boundaries. Images can be inspected with a graphical overlay of selected subregions. Bi-directional links between images and the index of structures are provided. In summary, we provide a novel content-rich digital atlas resource facilitating identification of morphological features relevant for delineating the anatomical subdivisions of the rat hippocampal region. The atlas application is available at http://www.rbwb.org.